Employee Performance Improvement at PT Cahaya Abadi Terang Medan Is Based on the Work Environment, Work Motivation, and Work Discipline - M. Sofyan Hasan Lubis; Yohny Anwar; Muhammad Isa Indrawan (Budapest International Research and Critics University, 2022)
This research discusses the partial or simultaneous effect of environment factors, motivation, and discipline on employee performance at PT Cahaya Abadi Terang. A questionnaire was used to gather data from 65 employees of PT Cahaya Abadi Terang. This paper uses multiple linear regression. The study findings demonstrate a substantial simultaneous effect between the three factors and a partly significant influence between environment, motivation, and disciplinary variables on employee performance.